Qualitative Analysis of the Technological Management for the Innovation of the Financial Services: Multiple Cases Study of Startups FinTech in Metropolitan Lima - Héctor Guardamino (2021)
This multiple-case study analyses, from a qualitative approach, the technological management for the innovation of the financial services in four startups FinTech from Metropolitan Lima in Peru: Apurata, Difondy, TasaTop and Tranzfer.me. The Six Facets model (Kearns et al., 2005) was used to assess the technological management processes of these FinTech. In addition, a rubric was developed from criteria and sub-criteria. Subsequently, thoroughly interviews were applied as a technique to collect information related to each of the six model processes (variables) and their respective principles (subvariables). On the other hand, the collected information was organized and systematized using the data content management software WebQDA. Finally, the results indicate that the Six Facets model is a potential tool to analyze the technological management processes that are developed in FinTech with internal technology areas. This in order to be able to find points of improvement whose solution contributes to the innovation of FinTech services, impacting its competitiveness. Likewise, among the studied FinTech, the most solid technological process is the planning, whereas the process in which the analyzed FinTech suffer the most is in the process of customer formation. Finally, it was determined that TasaTop is the most prepared FinTech for the innovation of its services.